Formulation and Evaluation of Floating Tablets of Pioglitazone Employing Calcium Starch - Chowdary, K.P.R.; Udaya Ch, D. (Asian Journal of Chemistry, 2011)
The objective of the study is to formulate and evaluate floating tablets of pioglitazone employing calcium starch, a new modified starch in comparison to hydroxy propyl methyl cellulose K15M, a synthetic cellulose derivative. Floating tablets of pioglitazone were prepared employing calcium starch and hydroxy propyl methyl cellulose, K15M as matrix formers, sodium bicarbonate as gas generating agent and bees wax as floating enhancer and the tablets were evaluated for in vitro buoyancy and drug release characteristics. Tablets formulated employing calcium starch (50 %), sodium bicarbonate (10 %) and bees wax (10 %) exhibited floating over 36 h with a floating lag time of 5-10 min. Pioglitazone release from the floating tablets formulated was slow, spread over more than 24 h and depended on the polymer used and its strength and concentration of sodium bicarbonate in the tablets. Drug release was diffusion controlled and followed first order kinetics. Fickian diffusion was the drug release mechanism from all the tablets formulated. Calcium starch gave slow, controlled and complete drug release in 24 h. Whereas hydroxy propyl methyl cellulose, K15M gave slow but incomplete drug release. Calcium starch was found to be a better matrix former than hydroxy propyl methyl cellulose for floating tablets.